2015
DOI: 10.1055/s-0035-1560043
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Severe Metabolic Bone Disease in Very Low-Birth-Weight Infants with Severe Bronchopulmonary Dysplasia Admitted to a Tertiary Referral Center

Abstract: Severe MBD was common in this referral-based cohort with severe BPD. The high incidence in this population is likely explained by the coexistence of multiple exposures and comorbidities associated with bone demineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
(29 reference statements)
2
7
0
1
Order By: Relevance
“…LOS remains an important problem and are associated with complications of preterm infants including BPD [27]. Jensen EA et al found that blood culture con rmed sepsis were associated with increased odds of severe MBD in infants with severe BPD [28]. Our study reenforced the association between LOS and MBD in BPD infants.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…LOS remains an important problem and are associated with complications of preterm infants including BPD [27]. Jensen EA et al found that blood culture con rmed sepsis were associated with increased odds of severe MBD in infants with severe BPD [28]. Our study reenforced the association between LOS and MBD in BPD infants.…”
Section: Discussionsupporting
confidence: 70%
“…BPD infants have a higher incidence (60% vs 34%, compared with infants without BPD) of MBD in infants 1,250 g [2]. Among infants born 1,500 g suffered from severe BPD, about one third developed severe MBD [3].…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that infants with bronchopulmonary dysplasia (BPD) have a higher incidence of MBD [2]. Among infants with birth weight < 1500 g suffered from severe BPD, about one third developed severe MBD [3].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term use of steroids and loop diuretics and limited mineral intake due to fluid restriction are recognized additional risk factors for metabolic bone disease in infants with BPD [ 95 ]. However, the ability of VLBW infants with early BPD to grow and accrete calcium was reported to be similar to that of those without early BPD [ 96 ].…”
Section: Nutritional Approach In the Prevention And Management Of Bpdmentioning
confidence: 99%